Materials procurement order development for feed manufacturing in a teaching and research farm in western Nigeria using multi-objective optimization approach (2018)
Although an essential but scarce resource, money is constantly required for the purchase of raw materials necessary for a continued production of livestock feeds. Improper management of available capital can lead to stoppage of production activities, low productivity and loss of customers’ good will. Therefore, there is the need to manage effectively the little capital available. This study was aimed at developing and solving a model that can determine the procurement order for raw materials considering the liquid capital constraint. An animal feed firm was investigated and data on materials (bill, quantity ratio, cost); products list; supplier’s list; product demand; liquid capital available and the available lead time amongst others were collected by means of interviews, observations and existing records. These were thereafter analysed to form the required parameters. A multi-objective optimization model was developed using linear programming technique as a tool for procurement order of materials in the firm and solved using two different soft wares (Tora 1.0 and Lingo 14.0). Selection of suppliers was based on payment term. 6 products, 13 materials, 7 suppliers, 2 days and ₦138,856 were obtained from the bill of materials, suppliers list, available lead time and liquid capital available respectively. A total weekly demand of 22,600kg of product was also obtained from the product demand. A total of 205 parameters were obtained from the analysed data. The developed model exhibited 3 objective functions (maximize profit on all products, minimize waiting time for all raw materials and minimize the total cost of raw material), 32 variables (Q1...q1) and 78 constraints (t1 ≤ 0.28… t13 ≥ 0). Same optimal values (0, 0, … and 0.55) were obtained from the use of Lingo 14.0 and Tora 1.0. Moreover, 211.97₦kg was realised as the optimum value for the objective function. The supplier IBM, with the most flexible payment term was selected to supply nine out of the 13 materials. The developed model will be useful in ensuring effective management of the available liquid capital for material procurement, thereby eliminating the stoppage of production activities, improving productivity and ensuring customers’ good will.